2020
DOI: 10.3390/ma13112661
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone/Gelatin/Hyaluronic Acid Electrospun Scaffolds to Mimic Glioblastoma Extracellular Matrix

Abstract: Glioblastoma (GBM), one of the most malignant types of human brain tumor, is resistant to conventional treatments and is associated with poor survival. Since the 3D extracellular matrix (ECM) of GBM microenvironment plays a significant role on the tumor behavior, the engineering of the ECM will help us to get more information on the tumor behavior and to define novel therapeutic strategies. In this study, polycaprolactone (PCL)/gelatin(Gel)/hyaluronic acid(HA) composite scaffolds with aligned and randomly orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Natural polymers from green plants are renewable [11,12]. Electrospinning of a polycaprolactone (PCL)/gelatin(Gel)/hyaluronic acid(HA) blended solution composite scaffold has been shown in recent studies to be an efficient technique for modifying PCL nanofibrous scaffolds for 3D glioblastoma cell culture [13]. Polycaprolactone (PCL), silver nitrate (AgNO3) and zinc oxide (ZnO) were used for the fabrication of a multilayered antibacterial nanocomposite material using coaxial electrospinning (CAE) as described by Guner CETIN et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Natural polymers from green plants are renewable [11,12]. Electrospinning of a polycaprolactone (PCL)/gelatin(Gel)/hyaluronic acid(HA) blended solution composite scaffold has been shown in recent studies to be an efficient technique for modifying PCL nanofibrous scaffolds for 3D glioblastoma cell culture [13]. Polycaprolactone (PCL), silver nitrate (AgNO3) and zinc oxide (ZnO) were used for the fabrication of a multilayered antibacterial nanocomposite material using coaxial electrospinning (CAE) as described by Guner CETIN et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many researchers focus on designing scaffolds with similar properties to human tissue on a nanoscale. Several studies have reported that large‐scale electrospinning can be produced using three‐dimensional connected porous nanofiber structures to resemble a native ECM network 136,137 . Gholipour Malekabadi et al designed new electrospun nanofiber scaffolds using electrospinning of different concentrations of silk fibroin solutions and evaluated their application for tissue engineering both in vitro and in vivo.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…[225][226][227][228] Synthetic materials such as PEG, alginate, PCL, polystyrene, polyacrylonitrile, and PDMS have been used as scaffolds and platforms to assess GBM migration and invasion, for their reproducibility and tunable mechanical properties. [229][230][231] However, because these materials lack biological recognition sites, they need to be functionalized with adhesive peptides or proteins to facilitate cell adhesion and growth. Alternatively, hybrid approaches that combine the biomimetic attributes of natural polymers with the tunable properties of synthetic poly-mers overcome these limitations in evaluating GBM invasion and therapeutic resistance.…”
Section: Hydrogel Scaffolds and In Vitro Platform Technologiesmentioning
confidence: 99%